Host plant range of a fruit fly community (Diptera: Tephritidae): does fruit composition influence larval performance?. Issue 1 (December 2016) - Hafsi, Abir; Facon, Benoit; Ravigné, Virginie; Chiroleu, Frédéric; Quilici, Serge; Chermiti, Brahim; Duyck, Pierre-François
Abstract Background Phytophagous insects differ in their degree of specialisation on host plants, and range from strictly monophagous species that can develop on only one host plant to extremely polyphagous species that can develop on hundreds of plant species in many families. Nutritional compounds in host fruits affect several larval traits that may be related to adult fitness. In this study, we determined the relationship between fruit nutrient composition and the degree of host specialisation of seven of the eight tephritid species present in La Réunion; these species are known to have very different host rangesin natura . In the laboratory, larval survival, larval developmental time, and pupal weight were assessed on 22 fruit species occurring in La Réunion. In addition, data on fruit nutritional composition were obtained from existing databases. Results For each tephritid, the three larval traits were significantly affected by fruit species and the effects of fruits on larval traits differed among tephritids. As expected, the polyphagous speciesBactrocera zonata, Ceratitis catoirii, C. rosa, andC. capitata were able to survive on a larger range of fruits than the oligophagous speciesZeugodacus cucurbitae, Dacus demmerezi, andNeoceratitis cyanescens . Pupal weight was positively correlated with larval survival and was negatively correlated with developmental time for polyphagous species. Canonical correspondence analysis of the relationship between fruit nutrient composition and tephritid survival showed that polyphagous species survived better than oligophagous ones in fruits containing higher concentrations of carbohydrate, fibre, and lipid. Conclusion Nutrient composition of host fruit at least partly explains the suitability of host fruits for larvae. Completed with female preferences experiments these results will increase our understanding of factors affecting tephritid host range.